Penerapan Project Based Learning Produk Poster Materi Norma untuk Meningkatkan Keterampilan Berpikir Kritis Siswa - Insanul Qisti Barriyah; Sutrisna Wibawa; Suhartini (Universitas Sarjanawiyata Tamansiswa, 2026)
Critical thinking is the main provision in the problem-solving process. Meanwhile, problem-solving ability is one of the peak aspects in education. So the need for special procedures to stimulate students' critical thinking in learning. This study aims to improve students' critical thinking skills through the Project Based Learning Poster Product model. The type of research used is PTK or Classroom Action Research. The subjects of the study were 16 fourth-grade students of SD Negeri Menggermalang, Samigaluh, Kulon Progo, Yogyakarta in the PPKn subject on norms and rules in daily life. Data were collected using observation instruments, written tests, and activity documentation. The results of this study indicate that after the implementation of the Project Based Learning poster product model there was a significant increase in students' critical thinking skills. The pre-cycle score showed 0% completeness, the first cycle post-test score showed 53.86% completeness, and in the second cycle showed 76.92% completeness. It can be concluded that the application of the Project Best Learning poster product model can significantly improve elementary school students' critical thinking skills.